Joseph Ratzinger’s Very Critical Diagnosis and Apology of the Catholic Church - Kaucha, Krzysztof (Verbum Vitae, 2023)
Many devoted and well-educated Catholics begin to doubt the need for the Church. Flooded by the plethora of publications about the Church’s dark pages and scandals in the past and today they feel pain and are ashamed. On the other hand, they realize that the Church can be neither a mistake nor a lie. Undoubtedly, Catholics and Catholic theology need today an honest and serious apology of the Catholic Church that will not conceal any of her true weaknesses. This paper seeks to prove that such an apology is offered by Joseph Ratzinger (1927–2022). It is an attempt to recreate it on the basis of his entire intellectual output. His diagnosis of the Catholic Church is bitterly critical, he indicates many ecclesial problems that seem to be carried over from one generation to the next. At the same time, he provides an original apology of the Catholic Church that can surely be helpful in accepting the bipolar truth about her: God’s real presence has been so many times mediated by the disappointing Church. This article’s final part attempts to critically evaluate the effectiveness of Ratzinger’s apology from the contemporary perspective of ardent Catholics.